Modeling depression with transgenic mice: the neurotrophin hypothesis revisited - Urani, Alexandre; Chourbaji, Sabine; Henn, Fritz A.; Gass, Peter (Clinical neuroscience research, 2003)
Based on clinical and experimental observations, the neurotrophin hypothesis of depression as conceptualized originally, made the following predictions: (i) reduced activity of the CREB-BDNF-TrkB pathway is implicated in the pathogenesis of depression; (ii) activation of the CREB-BDNF-TrkB pathway is part of the molecular mechanisms of antidepressive therapy. This concept has recently been challenged, at least in part, by studies with transgenic mice. According to the neurotrophin hypothesis, mice with genetical disruptions of any part of the CREB-BDNF-TrKB pathway would be expected to display depression-like behaviors. However, none of several mouse strains investigated so far have exhibited such a behavior, some of them being even less ‘depressive’ than the controls. Despite some possible explanations for the lack of a depression-like phenotype, the present findings challenge the hypothesis that this signaling pathway plays a major role in the pathogenesis of depression. However, mice with impaired CREB signaling show reduced BDNF inducibility. Moreover, mice with impaired BDNF-TrkB signaling have a decreased behavioral response to antidepressants. Thus, despite the conflicting results on the role of the CREB-BDNF-TrkB pathway in the pathogenesis of depression, this signaling cascade seems to be directly involved in the mechanisms of antidepressive therapy. Therefore, pharmacological strategies should be developed to generate small-molecule agents that increase the expression and promote the release of BDNF more specifically and more efficiently than currently available antidepressants.
Gesehen am 04.11.2020